Decolorization of Reactive Dyes by Spore-bound Laccase from Local Isolate of Bacillus sp. - AL-Sa'ady, Ali J. R.; N. Shukur, Yassamin; A. Hamod, Mohammed (Iraqi Journal of Science, 2023)
Utilization of bacterial activity for decolorization of coloured products is one the most promising industrial strategy, as an eco-sustainable and cost-competitive alter-native to physicochemical methods. Laccase production from Bacillus sp. was stud-ied for its decolorization influences on different dyes (Indian ink, Brilliant green, Bromothymol blue, Crystal violet, Safranin, Bromophenol blue, Methelen blue, Giemsa stain, Nigrosin, Toluidin blue, Neutral red, Phenol red, Hanna, Blood, Ben-gal rose B, Bromkresol green, 4-Bromoaniline, Aniline blue, 2,6-Dichlorophenol in-vophenol, Curcumin, Acridine orange, Indigo carmine, Xylene cynol FF,10G, Aliza-rine yellow GG and Kongorose). After 5 days of incubation of the spore-bound lac-case with different dyes, the maximum decolorization have seen in toluidin blue (89%), neutral red (84%), and indigo carmine (83%), brilliant green (82%) and acri-dine orange (82%), while the final percentage of degradation of other dyes were less than 65%. However, no additional redox mediator was added to the reaction, which suggests that this enzyme could be used in industries for effluents treatment. In addi-tion, our results indicate that the percentage of decolonization have decreased as the dyes concentrations were increased.